Proceso de atención de enfermería en paciente femenino de 36,6 semanas de gestación con preeclampsia. - Toro Angulo, Lady Tatiana (2021)
Preeclampsia is a pregnancy complication characterized by high blood pressure and signs of damage to another organ system, often the liver and kidneys. Mainly, preeclampsia begins after 20 weeks of gestation in women whose blood pressure was habitual. The rate of preeclampsia changes between 5% and 10% in developed nations, however this figure rises to 18% in certain territories developing. Preeclampsia persists as a leading cause of maternal and perinatal morbidity internationally. In Latin America, a quarter of maternal deaths have been associated with complications derived from gestational hypertensive disorders; Preeclampsia and eclampsia stand out as the main causes of maternal and perinatal morbidity and mortality. In Ecuador, pre-eclampsia is one of the most common complications in pregnant women, which means an important public health problem to take into account. About half of women with severe pre-eclampsia show up at the health center prior to 34 weeks' gestation, with an estimated fetal weight of less than 2000 grams.